(untitled) (Vietnam Journal of Community Medicine, 2026)
• Objectives: To describe the clinical and paraclinical characteristics and evaluate the efficacy of endocrine therapy combined with CDK4/6 inhibitors in patients with hormone receptor-positive, HER2-negative (HR+/HER2-) recurrent or metastatic breast cancer. • Methods: A combined retrospective and prospective descriptive study (involving clinical and imaging follow-up) was conducted on 32 patients diagnosed with HR+/HER2- recurrent or metastatic breast carcinoma. Data collection took place at the Department of Internal Medicine IV, Nghe An Oncology Hospital, from April 2023 to June 2026. The data cut-off date for analysis was June 10, 2026. The median follow-up duration was 9.7 months (with a minimum follow-up of 3.1 months). • Results: The mean age at the time of recurrence or metastasis was 58.09 years. The majority of patients had a good performance status (ECOG 0) at 78.1%; invasive ductal carcinoma accounted for 81.3%, and 81.3% had histological grade 2. The rate of late recurrence (more than 1 year after radical treatment) reached 65.6%. The most common metastatic or invasive sites included bone (56.3%), lung (56.3%), and peripheral lymph nodes (43.8%). The overall response rate (ORR) of the regimen was 37.5%; in which complete response was 3.1%, partial response was 34.4%, and stable disease was 37.5%, resulting in a clinical benefit rate (CBR) of 75.0%. The median progression-free survival (PFS) extended to 32.1 months. • Conclusion: The combination regimen of endocrine therapy and CDK4/6 inhibitors in patients with HR+/HER2- recurrent or metastatic breast cancer demonstrated favorable results regarding response rates and progression-free survival. This regimen proved feasible, was well-tolerated, and provided positive clinical benefits in a real-world clinical setting.